EFFECT OF FATIGUE ON EXPLOSIVE STRENGTH AND MUSCLE ARCHITECTURE OF THE VASTUS LATERALIS - Sousa,Matheus Martins de (2021)
ABSTRACT Introduction: There has been little research on changes in rate of torque development (RTD) and muscle architecture. This study evaluated the effect of fatigue on RTD and muscle architecture of the vastus lateralis (VL). Methods: Seventeen volunteers (25.5 ± 6.2 years; 177.2 ± 12.9 cm; 76.4 ± 13.1 kg) underwent isokinetic knee extension assessment at 30°/s to obtain the peak torque (PT-ISK), before and after a set of intermittent maximal voluntary isometric contractions (MVIC) (15 reps – 3 s contraction, 3 s rest) used to promote muscle fatigue, monitored by the median frequency (MDF) of the electromyography from the VL, rectus femoris and vastus medialis muscles. Before and after the fatigue protocol, ultrasound images of the VL were obtained to measure muscle thickness (MT), fascicle length (FL), and fascicle angle (FA). The peak isometric torque (PT-ISM) and the RTDs in 50 ms windows were calculated for each MVIC. The RTDs were reported as absolute values and normalized by the PT-ISM. Results: Fatigue was confirmed due to significant reductions in MDF in all three muscles. After the fatigue protocol, the PT-ISK was reduced from 239.0±47.91 to 177.3±34.96 Nm, and the PT-MVIC was reduced from 269.5±45.63 to 220.49±46.94 Nm. All the RTD absolute values presented significant change after the fatigue protocol. However, the normalized RTD did not demonstrate any significant differences. No significant differences were found in the muscle architecture of the VL. Conclusions: The reduction in explosive strength occurred concomitantly with the reduction in maximum strength, as evidenced by the lack of changes in normalized TDT. Level of Evidence III.